Diseño de un plan de mejoramiento para desarrollar un departamento aduanero de un grupo empresarial como empresa independiente en el distrito de Buenaventura (2013)
The present research work leads the reader to reveal the importance that must be had in the management of companies that are within the same business group, where the employers of the customs agencies must identify barriers that face this environment with in order to analyze the possible linkages that can be presented in the services sector and thus based on this information can be formulated strategies for the continuous improvement of the organizations. What is intended to develop the following degree work is to design an improvement plan to develop a customs department of a business group as an independent company in the district of Buenaventura, especially in planning, infrastructure, marketing, human resources and capital in the different areas of the customs agency SERCODEX SA, since there are currently deficiencies these variables for the development of daily activities that are carried out in such a prestigious organization.